Novel nanoparticulate systems for lung cancer therapy: an updated review. (3rd July 2017) - Madni, Asadullah; Batool, Amna; Noreen, Sobia; Maqbool, Irsah; Rehman, Faizza; Kashif, Prince Muhammad; Tahir, Nayab; Raza, Ahmad
Abstract: Lung cancer is the leading cause of cancer-related deaths in the world. Conventional therapy for lung cancer is associated with lack of specificity and access to the normal cells resulting in cytotoxicity, reduced cellular uptake, drug resistance and rapid drug clearance from the body. The emergence of nanotechnology has revolutionized the treatment of lung cancer. The focus of nanotechnology is to target tumor cells with improved bioavailability and reduced toxicity. In the recent years, nanoparticulate systems have extensively been exploited in order to overcome the obstacles in treatment of lung cancer. Nanoparticulate systems have shown much potential for lung cancer therapy by gaining selective access to the tumor cells due to surface modifiability and smaller size. In this review, various novel nanoparticles (NPs) based formulations have been discussed in the treatment of lung cancer. Nanotechnology is expected to grow fast in future, and it will provide new avenues for the improved treatment of lung cancer. This review article also highlights the characteristics, recent advances in the designing of NPs and therapeutic outcomes.